Dynamics of Subsurface Migration of Water on the Moon. Issue 5 (11th May 2021) - Reiss, P.; Warren, T.; Sefton‐Nash, E.; Trautner, R.
Abstract: We investigate the dynamics of a water pumping mechanism driven by temperature variations in the lunar subsurface. The thermal environment at three polar sites and three sites in the Clavius region was simulated, taking into account local terrain and scattered radiation. A separate heat and mass transfer model was used to simulate depth‐dependent, temperature‐dependent, and pressure‐dependent properties of the lunar subsurface. The results suggest that diurnally varying heat fluxes create suitable conditions for water migration at many sites across the lunar surface. Enabled by a constant supply to the lunar surface, water molecules typically migrate a few centimeters deep via the formation of distinct concentration peaks, and a downward flux driven by the repeated desorption and resorption. With a constant supply rate of 10 −15  kg/(m 2  s), the quantity of adsorbed water stored at Ga timescales reaches values on the order of 10 −10 to 10 −7  mol/m 2 at the investigated sites. Based on our results, we present a new relation for the water migration depth that takes into account the ratios of surface temperatures. The results of a sensitivity analysis show that the desorption activation energy is a dominant factor for the quantity and depth of water migration. In addition to long‐term accumulation of subsurface adsorbate, the model shows that temporarily captured water at shallower depths can be released during the lunar day at quantities of up to several µg m −2 . This, as well as exposure of shallow water disturbed by impacts, may be a relevant source for surface water in illuminated areas. Plain Language Summary: Water bound to the lunar soil is released by the daily temperature cycle on the Moon. A portion of it is subsequently lost to space, but some of it is transported to deeper layers in the lunar soil. How much water will be transported within the soil depends on the temperature distribution, timescales, and how strongly the water bonds with the soil. Using a simulation model for the heat exchange at the lunar surface and the heat and mass transfer within the lunar soil, we show how pronounced this phenomenon is at six selected sites in the lunar south polar region and the Clavius region. We find that the quantities of accumulated subsurface water are generally low, on the order of several micrograms per unit area, and tend to be higher at the polar sites. Subsurface water can be found at depths of only a few centimeters and the depth of the peak concentration can be determined using a newly established relation for surface temperature ratios. Such shallow accumulated water is also partly released during some lunar days and could in principle be observed during day at the surface, even at warmer mid‐latitudes, such as the Clavius region. Key Points: Our model combines 3D lunar surface temperatures and a detailed parametrization of heat and mass transfer properties of the subsurface Water typically accumulates at depths <10 cm with a distinct peak and migration depth can be estimated based on surface temperature ratios Water can be temporarily trapped at shallow depth even at mid‐latitudes, where it is partially released to the exosphere during day